(untitled) (Fiep Bulletin - online, 2012)
Introduction: Obesity is considered the biggest concern facilities accompanied by the achievements of the daily observed with advancing technology. It has also caused by multiple factors that result in excessive accumulation of fat in the body can be linked to the onset of diseases such as hypercholesterolemia, hypertriglyceridemia, hypertension, diabetes, appearing in childhood. Thus, early identification of childhood obesity is important, since the obese child can be tomorrow’s obese adult. Method: This paper aims to compare the data on the incidence of overweight and obesity in children aged 5 to 9 years of age with the National Health and Nutrition/PNSN (1989) and the Consumer Expenditure Survey 2008-09. Results: We observed increase in the percentage of overweight children in 20 years comparison (nearly from 9% to 33% from 1989 to 2008, respectively). Thus, in Brazil there was an increase in the incidence of overweight and / or obesity in children in just over 20% in the period 1989 to 2008. Observed a growth of 4.1% from 1989 in 2008 to 16.6% in boys and in girls from 2.4% to 11.8% in the same period. Conclusion: With respect to obesity grew significantly over the 20 years. We observed that the growth of childhood obesity has been linked to socio-cultural factors, an association of sedentary habits the lack of security, the pressure to consumption and the changes in contemporary families. So with all this complexity, it is necessary the intervention of various professionals in interdisciplinary teams in the treatment of obese children.